calculus

differentiate y = 2^3x^2

read as two to the 3x squared power

  1. 👍 0
  2. 👎 0
  3. 👁 159
  1. y=a^kx

    y'= k*a^(kx)*ln(a)

  2. y = 2^(3x^2)
    y' = ln2 * 6x * 2^(3x^2)

    it helps to go at it like this

    y = 2^(3x^2)
    ln y = 3x^2 ln2
    1/y y' = 6x ln2
    y' = ln2 6x 2^(3x^2)

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra 2

    I am so stuck on this factoring thing. how do you solve: 1)15a(squared)b-10ab(squared) 2)x(squared)-8x-8 3) 6p(squared)-17p-45 4)2r(cubed)+250 5)x(to the 6th power)-64 6)x(squared)-xy+2x-2y 7)x(to 4th power)-1

    asked by Cass on February 14, 2011
  2. Math

    Please help IF I am right or not Which of the following correctly simplifies the expression 3 to the power of 2 multiplied by 5 to the power of 0 whole over 4, the whole squared.? 3 to the power of 2 multiplied by 1 whole over 4,

    asked by Diana on March 6, 2018
  3. Math

    A few here. 4x-8 ------ x(squared)-4 _________________________ 2m(squared)+5m-3 ------------------ m(squared)+4m+3 __________________________ 3x+4 ----- 12 (times) 8 ----- 9x+12 ________________________ x+5 ----- 16x (divided by)

    asked by Maddi on June 8, 2010
  4. trigo help!

    1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)

    asked by I'm stumped on June 19, 2009
  5. math

    The math problem is........... 3n to the 2nd power when n=3 what do I do first if nothing is in parenthesis? Do I multiply 3n or do n to the 2nd power first? square n, then multiply it by three. That's a good question Nikki. We

    asked by Nikki on September 7, 2006
  1. Math help

    Someone please help me out on this polynomial!!! 2x(squared) y4(4th power)(2x(squared)y+2xy-3x(5thpower)y(3rd power)

    asked by Anonymous on February 17, 2014
  2. Math

    Find the shortcut. Solve these problems. Then find and explain a shortcut method for finding the answer. 52(Squared) - 42 (squared) = 82 (Squared) - 72 (Squared) = 122 (Squared) - 112 (Squared) = 312 (Squared) - 302 (Squared) =

    asked by Anonymous on December 4, 2014
  3. math

    How do i find the area of a triangle? For example: A squared + b squared= c squared 8.5 squared + 6.4 squared= c squared 72.25 + 40.96= c squared 113.21=c squared 10.6400188=c even tho i thought this was the answer it is not

    asked by samantha on August 29, 2008
  4. MATH

    My Math work instructions is place the numbers from least to greatest. 7 squared, 2, 8/2 squared = 2, seven squared, and 8/2 squared. 10 squared, pi, 3.5 = pi, 3.16, 3.5. 220 squared, -10, 100 squared, 11.5 = -10, 220 squared, 100

    asked by TAMARA on September 1, 2015
  5. math

    Which is equivalent to the expression (a squared + a to the fourth power) to the 0 power? a)0 b)1 c)a to the 6 power d)a to the eigth power I got answer a by adding 2 and 4 and multiplying it by 0. Is this right?

    asked by robert on January 31, 2008

More Similar Questions